A Fuzzy Reinforcement Learning Approach for Continuum Robot Control - Goharimanesh, M.; Mehrkish, A.; Janabi-Sharifi, F. (Journal of intelligent & robotic systems, 2020)
Continuum robots (CRs) hold great potential for many medical and industrial applications where compliant interaction within the potentially confined environment is required. However, the navigation of CRs poses several challenges due to their limited actuation channels and the hyper-flexibility of their structure. Environmental uncertainty and characteristic hysteresis in such procedures add to the complexity of their operation. Therefore, the quality of trajectory tracking for continuum robots plays an essential role in the success of the application procedures. While there are a few different actuation configurations available for CRs, the focus of this paper will be placed on tendon-driven manipulators. In this research, a new fuzzy reinforcement learning (FRL) approach is introduced. The proposed FRL-based control parameters are tuned by the Taguchi method and evolutionary genetic algorithm (GA) to provide faster convergence to the Nash Equilibrium. The approach is verified through a comprehensive set of simulations using a Cosserat rod model. The results show a steady and accurate trajectory tracking capability for a CR.